Neurovascular problems in the athlete's shoulder - Thompson, R. W.; Driskill, M. (Clinics in Sports Medicine, 2008)
Competitive athletes are subject to several neurovascular conditions that can affect the upper extremity. These conditions are relatively rare and can be difficult to recognize but are quite important because they can seriously limit athletic performance and may even have limb-threatening consequences. The purpose of this article is to review how to identify and differentiate the major neurovascular conditions affecting the upper extremity in the athlete-patient. We also wish to highlight current concepts and treatment strategies for these problems that can help avoid serious complications and promote successful outcomes. Indeed, with early recognition, proper initial treatment, and prompt referral for comprehensive surgical care, most athletes with these conditions can return to previous levels of performance within several months of diagnosis and definitive treatment.